Self subcutaneous injection of profenophos with delayed systemic toxicity: a case report - Hanushraj R.; Sudharsan S. (International Journal of Medical Research and Review, 2016)
Suicidal poisoning by ingestion of organophosphate (OP) insecticide is a common mode of poisoning in our region. However, attempted suicide via the parenteral route has rarely been reported. We report a case of self subcutaneous injection of 50% profenophos in both hands, a rare and unusual way of intoxication. It causes local toxicity such as toxic cellulitis, abscess and necrosis with delayed systemic toxicity. He responded to parental antibiotics, surgical debridement, atropine and pralidoxime.